Orchestrating green ports: An integrated BWM–Fuzzy DEMATEL–ANP–TOPSIS framework for techno-economic prioritization - Hoang Dat Do; Do Duc Anh Le; Thi Thai Le; Thi Kim Tin Nguyen; Thanh Tam Le; Thi Hoang Oanh Truong (Center of Biomass & Renewable Energy (CBIORE), 2026)
This study introduces a comprehensive multi-criteria decision-making framework that integrates the Best–Worst Method (BWM), fuzzy DEMATEL, the Analytic Network Process (ANP), and TOPSIS to prioritize green port electrification and operational enhancements. The model reflects complex trade-offs that shape decarbonization plans by asking experts about 20 important techno-economic, environmental, and organizational factors. The most important results show that emission abatement, fuel savings, and pollution reduction had the highest BWM weights. This shows that environmental goals are the most important. Fuzzy DEMATEL research showed that lifecycle replacement risk and labor preparedness were the main factors that affected tariff exposure, operational dependability, and digital integration results. ANP adjusted the weights of the criteria to take into consideration interdependencies, making economic risk and human capital the most important factors in decision-making. The TOPSIS rating found that a hybrid phased deployment option was the best choice for meeting goals for cost, emissions reduction, and operational readiness. It did better than both electric and traditional methods. These results show that the framework may combine expert knowledge, causal structure, and network feedback to make green port techniques more important. The concept goes beyond linear weighing by using cause-and-effect maps and feedback loops. This gives decision-makers a better understanding and more confidence when it comes to allocating resources. The results encourage a balanced growth of capital investments, environmental protection, and the ability of the workforce. This flexible strategy is helpful in gradually combining the renewables, tariff dynamics, and operational data to create strong, low-carbon marine logistics centers.